From face-to-face learning to web base learning: How are student readiness? - Arif Widodo; Nursaptini Nursaptini; Setiani Novitasari; Deni Sutisna; Umar Umar (Universitas PGRI Madiun, 2020)
Learning readiness influences learning success. Changing the learning model requires preparation. Well-planned online learning is different from learning in an emergency. This study aims to determine the readiness of student learning in online learning during the Covid-19 pandemic. The type of research used non-experimental quantitative. The data collection method is done by survey. Data analysis uses descriptive statistics. The subjects in this study were PGSD students at Mataram University. The number of respondents involved 260. Problems in this study include: how are students' learning readiness? what are the problems faced by students? Can students take part in online learning well? The results showed that students' learning readiness was still lacking. Students experiencing technical obstacles include lack of online media mastery, no training, limited costs, and difficulties in internet connection. Most students expect online learning to stop and come back face to face.